Establishing the Vital Role of Administrative and Instructional Support - Airel M. Coligado; Rufino T. Tudlasan (Journal of Innovation in Education and Social Research, 2025)
This study assessed the administrative and instructional support provided to Grade 10 TLE – SMAW students at Cabancalan National High School, Mandaue City, Cebu during S.Y. 2024-2025 as basis for an enrichment plan. A descriptive-correlational research design was employed, utilizing an adapted and modified questionnaire to gather data on teacher and student demographics, the level of administrative and instructional support, and students' skills performance in welding process and execution, safety compliance, work quality and accuracy, and employability. Findings revealed that teachers were female, aged 31-40, married, with at least a master’s degree, 6 to 10 years of service, and an outstanding performance rating, with national certificate level and national level training. The students were primarily male, aged 15-17. The level of administrative and instructional support was found to be moderately demonstrated, while students' skills performance was rated outstanding in work quality and accuracy and very satisfactory in other areas. A significant relationship was found between administrative and instructional support and students' skills performance. Based on the findings, it is recommended to implement the SMAW Enrichment Plan to further improve instructional strategies, resource allocation, and student competency in welding.